Perempuan Pengerajin Bidai di Perbatasan Jagoi Babang - Nikodemus Niko (Raheema, 2016)
Development urgency in the border area is can not touches all of community aspects in life. While the implementation of development is not equal for people who live in the border area. This paper described about women empowerment of Bidai plaiting. One of the community business border rely on local resources is the product of Bidai. This paper using secondary of the data and field observation, then analized in the form of descriptive research. Based on the field data and analysis showing that the government and stakeholder is to be an effort to community empowering, mainly woman in the developing business of Bidai craft.